Current Status and Perspectives of Protease Inhibitors and Their Combination with Nanosized Drug Delivery Systems for Targeted Cancer Therapy - Rudzińska M; Daglioglu C; Savvateeva LV; Kaci FN; Antoine R; Zamyatnin Jr AA (Dove Medical Press, 2021)
Magdalena Rudzińska,1 Cenk Daglioglu,2 Lyudmila V Savvateeva,1 Fatma Necmiye Kaci,3 Rodolphe Antoine,4 Andrey A Zamyatnin Jr1,5,6 1Institute of Molecular Medicine, Sechenov First Moscow State Medical University, Moscow 119991, Russia; 2Biotechnology and Bioengineering Application and Research Center, Integrated Research Centers, Izmir Institute of Technology, Urla, Izmir 35430, Turkey; 3Department of Molecular Biology and Genetics, Faculty of Science, Erzurum Technical University, Yakutiye, Erzurum 25050, Turkey; 4CNRS, Institut Lumière Matière, Univ Lyon, Université Claude Bernard Lyon 1, Lyon F-69622, France; 5Belozersky Institute of Physico-Chemical Biology, Lomonosov Moscow State University, Moscow 119991, Russia; 6Department of Biotechnology, Sirius University of Science and Technology, Sochi 354340, RussiaCorrespondence: Magdalena Rudzińska; Andrey A Zamyatnin JrInstitute of Molecular Medicine, Sechenov First Moscow State Medical University, Moscow 119991, RussiaTel +74956229843Email magdda.rudzinska@gmail.com; zamyat@belozersky.msu.ruAbstract: In cancer treatments, many natural and synthetic products have been examined; among them, protease inhibitors are promising candidates for anti-cancer agents. Since dysregulated proteolytic activities can contribute to tumor development and metastasis, antagonization of proteases with tailored inhibitors is an encouraging approach. Although adverse effects of early designs of these inhibitors disappeared after the introduction of next-generation agents, most of the proposed inhibitors did not pass the early stages of clinical trials due to their nonspecific toxicity and lack of pharmacological effects. Therefore, new applications that modulate proteases more specifically and serve their programmed way of administration are highly appreciated. In this context, nanosized drug delivery systems have attracted much attention because preliminary studies have demonstrated that the therapeutic capacity of inhibitors has been improved significantly with encapsulated formulation as compared to their free forms. Here, we address this issue and discuss the current application and future clinical prospects of this potential combination towards targeted protease-based cancer therapy.Keywords: proteases, inhibitors, nanoscale drug-delivery system, combination therapy, cancer treatment